IMPLEMENTATION OF EXPERIENTIAL LEARNING MODEL ASSISTED BY INTERACTIVE GAMES TO IMPROVE LEARNING INTEREST CONCEPT UNDERSTAND SKILLS - Fatikhah, Findi Auliya; Gunawan, Gunawan; Ahmad, Ahmad; Kusuma, Jaka Wijaya; Widiyastuti, Erni (Yayasan Education and Social Center, 2025)
This study aims to test the effectiveness of the implementation of the interactive game-assisted experiential learning model in improving the learning interest and skills to understand mathematical concepts of students in grade VIII B SMP Negeri 2 Kembaran. This research uses the classroom action research method which is implemented in two cycles. The research subjects were 32 students, with data collection techniques through observation, interviews, and documentation. The results of the study showed a significant increase in students' interest in learning and skills to understand mathematical concepts. In the first cycle, the average learning interest reached 68.00 (medium category) and increased to 78.00 (high category) in the second cycle. The skills to understand mathematical concepts has also increased, with the average test score in the first cycle of 67.50 and increased to 75.00 in the second cycle. The classical learning completeness of students reached 74.00%, meeting the PTK success indicator of 70.00%. The study concluded that the interactive game-assisted Experiential Learning model was effective in increasing students' interest in learning and understanding of mathematical concepts.